Big Data and Audit Quality: Theoretical Study - Hima, Zakaria; Yusoff, Wan Sallha; Saraih, Ummi Naiemah binti (South Asian Journal of Social Sciences and Humanities, 2024)
This paper provides an extensive examination of academic research focusing on the application of  big data in relation to audit quality. The literature review is derived from published articles in  auditing-related journals. Our review is structured around three primary impacts of applying big  data in accounting, auditing, and audit quality. Within each effect, we delve into the findings  pertaining to the quality of audits and financial reports. We assert that the limited empirical  evidence, coupled with recent technological advancements in information technology, creates  opportunities for future research to explore the significant effects of big data application on audit  quality and auditing in a broader context.
Keywords: Big data application; accounting, auditing; audit quality; information technology; information technology audit quality